New Landscapes of Religion in the West - Fauzia Ahmad (International Institute of Islamic Thought, 2001)
Set within the grand and lush surroundings of Mansfield College, Oxford University, and hosted by the Department of Geography, this conference, held between September 27-29,20o0, attracted some of Europe’s key academics from such varied disciplines as human geography, social anthropology, theology, and sociology. They met to discuss the creation and assertion, by minorities, of religious spaces in the West. About thirty to thirty-five participants discussed both empirical data and theoretical debates within the contexts of multiculturalism, identity, and minority rights. Out of twenty-one papers, eight specifically dwelt on Muslim communities and spaces, nine were of a more general nature, focusing either on historical or general overviews or theoretical issues, while four concentmted on Hindu and Sikh movements in the West. Much of the work presented was derived from projects conducted as part of the ESRC’s Research Program on Transnational Communities, which is directed by Steve Vertovec who is in the Faculty of Anthropology and Geography at the University of Oxford. Vertovec, who is editor of Muslim European Youth (1998), and Ceri Peach were joint editors of Islam in Europe (1997). The conference began with a keynote address from Diana Eck of Harvard University describing The Pluralism Project of which she was director. The project had three main aims: first, to document the increasing religious diversity and changing religious landscape and demography of American cities; second, to study how religious communities are changing; and third, to assess how American society is adapting to a multireligious reality. She described how the conversion of old buildings to the development of purpose- built centers such as mosques, temples, and gurdwaras marked an architectural reality that served to acknowledge the United States as a pluralist society. Muslim communities in the US, she noted, numbered between five to seven million-almost as numerous as the Jewish population, and more than some Christian sects. She stressed the dynamism of community adaptations and the existence of some ‘ethnic enclaving.’ The ...